Creation of a Comprehensive Training and Career Development Approach to Increase the Number of Neurosurgeons Supported by National Institutes of Health Funding. (16th November 2020) - Smith, Luke; Rezaizadeh, K. Paul; Tennekoon, Michael; Ojemann, Jeffrey A; Lonser, Russell R; Korn, Stephen J
Abstract: INTRODUCTION: Due to financial pressures, lack of community support, and a dearth of in-training cirricula, there was a paucity of National Institutes of Health (NIH)-funded neurosurgeons in the early 2000's. To increase the number of independent NIH-funded neurosurgeons the National Institute of Neurological Disorders and Stroke (NINDS) developed national comprehensive collaborative programs, the R25 and K12 programs, to support in-training and early career neurosurgeons. METHODS: This is a cohort study of neurosurgeon-scientists (in-training and faculty) pursuing NIH funding. The period from 2009 to 2019, the years after institution of the R25 and K12 training programs, was analyzed. Growth in the number of neurosurgeons who obtained NIH career development (K), independent (R01/DP) and collaborative research (U/P) awards after implementation of these NINDS-initiated programs was calculated over this time period. RESULTS: Between 2009 and 2019, the NINDS R25 funded 87 neurosurgical residents. Fifty-three (61%) have completed the award and training and 39 (74%) are in academic practice. Compared to neurosurgeons that did not receive R25-funding, R25 awardees were twice as successful (64% versus 31%) in obtaining K-awards and received the K-award in a significantly shorter period of time after training (25.2 ± 10.1 versus 53.9 ± 23.0 months; P < . 004). Between 2013 and 2019, the NINDS K12 has supported 19 neurosurgeons. Thirteen (68%) have finished their K12 support and all (100%) have applied for federal funding. Eleven (85%) have obtained major individual NIH grant support. Since establishment of these two programs, the number of unique neurosurgeons supported by either individual (R01 or DP-series) or collaborative (U- or P-series) NIH grants increased from 36 to 83 (2.3-fold increase). CONCLUSION: Targeted research education and career development programs initiated by NINDS led to a rapid and dramatic increase in the number of NIH-funded neurosurgeon-scientists and total NIH neurosurgery department funding.